HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN STATUS GIZI BAYI USIA 7-12 BULAN DI KECAMATAN TANETE RIATTANG BARAT KABUPATEN BONE - Hasnidar (Jurnal Suara Kesehatan, 2015)
ABSTRACT: "Exclusive Breastfeeding Relationship With Nutritional Status Babies 7-12 Months In Sub Tanete Riattang West County Bone". Exclusive breastfeeding and nutritional status is very important because breast milk nutritious or not depends on the type of food that is nutritious. This study aims to determine exclusive breastfeeding, nutritional status and determine the relationship of exclusive breastfeeding and nutritional status of infants aged 7- 12 months in the district of West Riattang Tanete Bone regency.The method used is a kind of quantitative data obtained through observation, interviews and documentation, then analyzed the data analysis of univariate in the form of frequency distribution table that statistical tests that have been done, then the p value = 0.000 so that it can be concluded that there is a relationship between breastfeeding exclusive to the nutritional status of infants aged 7-12 months. Results of the research that the majority of infants aged 7-12 months receive exclusive breastfeeding at 35 infants (61.4%). Most infants aged 7-12 months have good nutritional status are 44 infants (77.2%). Based on statistical tests that have been done, then the p value = 0.000 so that it can be concluded that there is a relationship between exclusive breastfeeding and nutritional status of infants aged 7-12 months.